Revisiting Okun’s Law: Evidence from Malaysia - Nasir, Syahira; Jamaludin, Salwaty; Safian, Sharul Shahida Shakrein; Malek, Nazurah Abdul; Abdul Aziz, Muhammad Ridzuan (Information Management and Business Review, 2024)
Okun’s Law explains an inverse relationship between unemployment and GDP. To re-examine the validity of Okun’s Law to the Malaysian economy through the period of 1988 until 2021, this paper employed the Ordinary Least Squares (OLS) approach with several diagnostic tests. The findings indicate that there is a significant relationship between GDP and unemployment. The control variables - population, inflation rate, and FDI also significantly affect unemployment. While the country’s GDP and inflation rate have a negative relationship with unemployment, population and FDI have a positive relationship with unemployment in Malaysia. Therefore, Okun’s Law is valid in the case of Malaysia.